Pengaruh Aromaterapi Lavender terhadap Pengurangan Tingkat Kecemasan pada Pasien Pra-Operasi Fraktur di Ruang Rawat Inap RSUD Wonosari: - ARYANTI, RIANA (Poltekkes Kemenkes Kupang, 2025)
Anxiety management in fracture patients is generally done with pharmacological therapy, but there is a risk of side effects such as drowsiness and dependence. Lavender aromatherapy, which contains linalool and linalyl acetate, has been shown to be effective in lowering anxiety through its relaxing effects on the central nervous system. A preliminary study at Wonosari Hospital showed that most fracture patients experienced moderate to high anxiety, with intervention still limited to sedatives. This study aims to evaluate the effect of lavender aromatherapy using a diffuser for three days on the reduction of anxiety levels in fracture patients in the inpatient room. This study uses the Case study research with the design of One Group Time Series Design in fracture patients at Wonosari Hospital. The sample was taken by purposive sampling of 2 respondents with the APAIS instrument to measure the level of anxiety before and after the intervention. The intervention was carried out three times a day using a diffuser with a dose of 5 drops (0.25 ml in 100 ml of water) for 15 minutes. The results of the study showed that lavender aromatherapy was effective in significantly reducing anxiety in fracture patients. The anxiety scores in pre-test and post-test 1 were in the severe anxiety category, while a significant decrease occurred in post-test 2 and was more optimal in post-test 3 with the anxiety category decreasing to moderate. The progressive reduction in anxiety shows that the lavender aromatherapy intervention is effective in working gradually in providing a sense of calm to the patient.